2014
DOI: 10.1371/journal.pone.0113137
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Limitation and Slow Drying Induce Desiccation Tolerance in Conjugating Green Algae (Zygnematophyceae, Streptophyta) from Polar Habitats

Abstract: BackgroundFilamentous Zygnematophyceae are typical components of algal mats in the polar hydro-terrestrial environment. Under field conditions, they form senescent vegetative cells, designated as pre-akinetes, which are tolerant to desiccation and osmotic stress.Key FindingsPre-akinete formation and desiccation tolerance was investigated experimentally under monitored laboratory conditions in four strains of Arctic and Antarctic isolates with vegetative Zygnema sp. morphology. Phylogenetic analyses of rbcL seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 54 publications
8
85
0
Order By: Relevance
“…Kim et al ., 2008, 2011; Holzinger et al ., 2009). In this study, we confirmed the occurrence of Zygnemopsis (Pichrtová et al ., 2014 b ), and further determined the species as Zygnemopsis lamellata by morphological characterization of a fertile sample observed in the field.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Kim et al ., 2008, 2011; Holzinger et al ., 2009). In this study, we confirmed the occurrence of Zygnemopsis (Pichrtová et al ., 2014 b ), and further determined the species as Zygnemopsis lamellata by morphological characterization of a fertile sample observed in the field.…”
Section: Discussionmentioning
confidence: 99%
“…2013; Pichrtová et al . 2013, 2014 b ). In another filamentous conjugating green algal genus, Spirogyra , molecular diversity analysis of sterile strains from Germany and Austria revealed 53 different SSU rDNA genotypes within 130 isolated strains, and the genus was split into eight independent lineages (Chen et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations